Pemberdayaan UMKM dalam Mengoptimalkan Sosial Media untuk Memasarkan Produk - Jahroni Jahroni; Mohammad Gilang Ramadhan; Jawahirul Maknuun (Lembaga Pengembangan Kinerja Dosen, 2025)
Community service activities (PKM) located in Kempreng Rt26Rw 02, Tanjungsari village, Taman District, Sidoarjo Regency. This community service activity (PKM) aims to empower MSMEs in optimizing social media to market products, then provide direction so that MSME actors have and optimize social media accounts for business or can use them effectively and efficiently. This activity is expected to provide understanding and the ability of MSME actors in Bakar Rama and Seblak julid in using social media optimally so that it has an impact on business development and increases profits. This activity uses the Participatory Action Research (PAR) approach method which includes: interviews to find out the SWOT or problems faced by MSME actors in Bakar Rama and Seblak julid related to social media, making posters of product menus sold then making content about the products they sell, creating social media accounts and optimizing them. This PKM activity has been carried out smoothly according to the goals to be achieved, and getting good results. The results of this activity are that MSME actors understand how to use social media optimally, expand sales, and the products sold can be known to many people. However, there is one MSME that is less interested in using social media other than WhatsApp.